مدى تقبل الأطفال لبيئتهم الصفية في الرياض الحكومية والأهلية (Journal Of Educational and Psychological Researches, 2014)
The research aimed at measuring the degree to which the accept their class environment in governmental & civil Kindergartens &  it also aimed at knowing the differences between the dimensions of the measurement & the differences according to the kindergarten & class variables .The researcher made a measurement for the class environment & it included five dimensions & the answering choices were three ( to a big extent , to some extent and no ) and after making sure that the measurement is usable , the researcher applied it on the sample which consisted of ( 212 )male & female children through the estimated answers of the teacher & the result was that there was an acceptance of the children to their environment , & also their were differences in three dimensions of the measurement in favor of the research sample .Also , there was a difference in the other two dimensions in favor of society whereas there was no difference showing the children's acceptance to their environment according to the kindergarten & class variables . In the light of the results of the research , the researcher asks for making an atmosphere of intimacy , love & amusement between the teacher & the child .